Creating a novel approach to discourse treatment through coproduction with people with aphasia and speech and language therapists. Issue 10 (3rd October 2022) - Cruice, M.; Aujla, S.; Bannister, J.; Botting, N.; Boyle, M.; Charles, N.; Dhaliwal, V.; Grobler, S.; Hersh, D.; Marshall, J.; Morris, S.; Pritchard, M.; et al.
ABSTRACT: Background: Although spoken discourse is an outcome prioritised by all stakeholders in aphasia rehabilitation, assessment and treatment of discourse are not routine clinical practice. The small evidence base, varied clinical expertise, multiple barriers in the workplace, and challenges for clients in understanding their altered language abilities all contribute to this situation. These factors need serious consideration when developing a new treatment. Involving intended stakeholders as partners in the development process is recommended. This assists with future implementation by ensuring assessment and treatment are practical, feasible, and acceptable to those who will deliver and undertake it. Aims: This paper reports on the coproduction phase of the Linguistic Underpinnings of Narrative in Aphasia (LUNA) research project and describes the levels of partners' involvement, the outcomes and impact of coproduction, and the factors that influenced it. Methods and procedures: Four partners with aphasia and four speech and language therapists (SLTs) worked with academic team members across a 6-month period to create the LUNA assessment and treatment. Separate sessions were held with partners with aphasia (monthly) and SLTs (fortnightly). Coproduction methods included open discussion, the Someone Who Isn't Me (SWIM) technique (thinking from others' perspectives), low and high fidelity prototypes, flexible brainstorming, card sort, and active experimentation with assessment and treatment tasks. Verbal and written information was presented, shared and documented during each session in supportive formats, and each session summarised as accessible minutes. Outcomes and Results: Partners contributed at consultation, cooperation, and co-learning levels during the coproduction phase. Outcomes included joined-up thinking across assessment-goal setting-treatment-desired outcomes; agreed decisions and content for assessment protocol and treatment manual; clarity on personalised, meaningful, and relevant treatment; therapeutic alliance operationalised in treatment manual; and more. Impacts included increased confidence, self-knowledge, pride, validation, peer support, networking, and benefits to SLTs' services. Coproduction was positively influenced by consistent session structure and conduct, group dynamics, accessible communication methods, active task experimentation, and SWIM technique. Although the process was time and labour intensive, all partners considered this worthwhile. Conclusions: LUNA has exemplified how an inclusive coproduction process can work well despite the language challenges of aphasia. Authors also believe that coproduction with intended users has resulted in products (assessment protocol, treatment manual) that are more practical, feasible, and acceptable to clinicians and clients than if designed by academics alone. This latter claim now needs testing on a wide scale.